(untitled) (Journal of Engineering, 2024)
In the past years, the use of composite materials in the aircraft industry, among others, has grown immensely Composite systems offer an advantage over traditional aircraft materials (metals) because they tend to exhibit higher strength/weight and stiffness/weight ratios than metals, thus making the aircraft lighter and improving performance. Woven composites are increasingly considered for such applications because they offer ease in manufacturing of complicated geometries, but the mechanical properties for different weave patrons of the material is even less well characterized than that of non-woven (angle-ply) laminates For this reason and because the woven composite mechanical properties is impotent for the theoretical work of the presented work way. The woven factors were evaluated and measured for the composite with different weave patrons, fiber materials and matrix materials. The woven factors were calculated from the measuring mechanical properties from tensile tests of woven composite and for the cross- unidirectional composite made from the same materials. Three types of fiber were used which are E-Glass, Kevlar, and Carbon, while epoxy and polyester were used as a matrixes The results showing that the woven factors for the Kevlar is higher than the E-Glass and the Carbon and the composites reinforce epoxy have higher woven factors than the composites reinforced polyester.